Beyond "Math Is Hard": A Systematic Review of the Integration of Philosophy in Mathematics Education - Nursit, Isbadar; Fathani, Abdul Halim; Widiyanti, Ria; Doluubeng, Muhamad Yusri (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study reviews students’ negative perceptions of mathematics and examines how philosophies of mathematics education shape perceptions and teaching practice. Using a PRISMA-2020–based Systematic Literature Review, authors searched Scopus, Web of Science, ERIC, and Google Scholar and applied inclusion criteria: peer-reviewed full-text articles published between 1992 and 2024. Thirty-two studies were thematically analyzed. Findings show constructivism and humanism as the most prevalent approaches, while ethnomathematics is widely implemented within local cultural contexts in Asia and Latin America. Integrating these philosophies boosts students’ motivation, interest, and confidence, though perceptions of mathematics as abstract are not fully dispelled. Teachers cite curriculum pressure, limited training, and insufficient policy support as key barriers. The review underscores the urgency of grounding reflective pedagogy in the philosophy of mathematics education to improve students’ perceptions and learning experiences across contexts. Realism appears less dominant in classroom practice, highlighting the need for sustained policy backing and professional development.